2020
DOI: 10.3390/su12114776
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach Using MLP and SVM Algorithms for the Fault Prediction of a Centrifugal Pump in the Oil and Gas Industry

Abstract: The demand for cost-effective, reliable and safe machinery operation requires accurate fault detection and classification to achieve an efficient maintenance strategy and increase performance. Furthermore, in strategic sectors such as the oil and gas industry, fault prediction plays a key role to extend component lifetime and reduce unplanned equipment thus preventing costly breakdowns and plant shutdowns. This paper presents the preliminary development of a simple and easy to implement machine learning (ML) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(71 citation statements)
references
References 53 publications
0
51
0
2
Order By: Relevance
“…The SVM uses a margin, the distance between these support vectors, to find the optimal decision boundary. It is very important to select the proper kernel function as it explains the feature space where the training data will be classified [36].…”
Section: Support Vector Machinementioning
confidence: 99%
“…The SVM uses a margin, the distance between these support vectors, to find the optimal decision boundary. It is very important to select the proper kernel function as it explains the feature space where the training data will be classified [36].…”
Section: Support Vector Machinementioning
confidence: 99%
“…The authors concluded that the k-NN algorithm along with a GA could be a reliable diagnostic tool for bearing condition monitoring. The support vector machine (SVM) and multilayer perception (MLP) algorithms were used in [ 34 ] to analyze centrifugal pump seal leakages. The authors used the accelerometer data collected from the installation site over four years.…”
Section: Introductionmentioning
confidence: 99%
“…The paper also presents the progress of different types of models analyzing seven algorithms with the use of WEKA software. The data mining approach that takes place in paper [22] can help transform maintenance processes on Greek railways. The paper [22] presents the development of a simple and easy to be used model for the prediction of an early damage of an oil pump at the oil and gas industry.…”
Section: Introductionmentioning
confidence: 99%
“…The data mining approach that takes place in paper [22] can help transform maintenance processes on Greek railways. The paper [22] presents the development of a simple and easy to be used model for the prediction of an early damage of an oil pump at the oil and gas industry. The data analysis is based on real historic data from sensors.…”
Section: Introductionmentioning
confidence: 99%